Two Cases of Arnold-Chiari Malformation with Respiratory Failure - Sinem Iliaz; Raim Iliaz; Mustafa Erelel (European Journal of Case Reports in Internal Medicine, 2014)
Arnold–Chiari malformation is defined as downward displacement of the brainstem and cerebellum through the foramen magnum. It has different clinical presentations and four subtypes. It is known that downward migration of posterior fossa components through the foramen magnum and associated lower cranial nerve palsy and brainstem compression can cause respiratory failure. Acute respiratory failure could mark the onset of the disease. Posterior fossa decompression performed to treat primary disease can improve the central sleep abnormalities. As respiratory failure is rarely seen, this paper presents two cases of Arnold–Chiari malformation with respiratory failure.